2021
DOI: 10.1136/bmjopen-2020-048551
|View full text |Cite
|
Sign up to set email alerts
|

Rabies mortality and morbidity associated with animal bites in Africa: a case for integrated rabies disease surveillance, prevention and control: a scoping review

Abstract: ObjectiveThe objective of this scoping review was to map the current situation and available evidence and gaps on rabies morbidity, mortality, integrated rabies surveillance programmes, and existing prevention and control strategies in Africa.MethodsWe conducted a systematic scoping review following the Joanna Briggs methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews checklist. Medline, Embase, CINAHL (EBSCOHost), Scopus, Web of Science and rabies w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 110 publications
0
33
0
Order By: Relevance
“…The population largely remains ignorant of the risk of rabies in Mauritania and elsewhere [7]. In the literature, almost all studies conducted in different parts of the world showed that dog is the main vector in Africa, Asia, and Latin America [7,[9][10][11]. The incubation period observed in our two cases was 20 and 55 days, respectively.…”
Section: Case Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The population largely remains ignorant of the risk of rabies in Mauritania and elsewhere [7]. In the literature, almost all studies conducted in different parts of the world showed that dog is the main vector in Africa, Asia, and Latin America [7,[9][10][11]. The incubation period observed in our two cases was 20 and 55 days, respectively.…”
Section: Case Discussionmentioning
confidence: 53%
“…In Mauritania, rabies has been known to exist, but reliable epidemiological data on rabies are absent. Many cases of rabies in developing countries are not diagnosed with laboratory confirmation and are often not even reported to health authorities [10]. The affected subjects usually die without appropriate care at home, without diagnosis being made.…”
Section: Case Discussionmentioning
confidence: 99%
“…In Mauritania, rabies has been known to exist, but reliable epidemiological data on rabies are absent. Many cases of rabies in developing countries are not diagnosed with laboratory confirmation and are often not even reported to health authorities 13 . Bite victims often do not receive appropriate prophylactic care due to patients' ignorance, lack of awareness among health workers, lack of necessary biological products, or insufficient means to pay the cost of preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of rabies in developing countries are not diagnosed with laboratory confirmation and are often not even reported to health authorities. 13 Bite victims often do not receive appropriate prophylactic care due to patients' ignorance, lack of awareness among health workers, lack of necessary biological products, or insufficient means to pay the cost of preventive treatment. The affected subjects usually die without appropriate care at home, without diagnosis being made.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier review in similar endemic settings has generated evidence on the status of the rabies and identified the gaps and challenges in prevention and control measures, summarised on the rabies measures which have shown promises and finally recommended adoptable innovations. 30 The current review aims to come up with such findings specific to Bangladesh which will in the future guide the country’s strategy in eliminating rabies. Reiterating the challenge to have basic information on rabies burden to comparative information related to efficiency of public health measures, control strategies and different vaccines and cost-effectiveness of pharmacological interventions, the review will establish an evidence base on rabies status in human, disease impact, knowledge and practice among people, effective prevention and control measures to support the national rabies action strategies.…”
Section: Implication Of the Reviewmentioning
confidence: 99%